THE EFFECT OF DIFFERENT C:N AND C:P RATIO OF MEDIA ON THE CONTENT OF POLYHYDROXYBUTYRATE IN BIOFLOC INOCULATED WITH BACTERIUM Bacillus cereus - Supono .; Johannes Hutabarat; Slamet Budi Prayitno; YS Darmanto (JOURNAL OF COASTAL DEVELOPMENT, 2013)
Biofloc technology  has  added values in aquaculture management, both in water quality  management and feeding  management.  As an optional feed, biofloc is capable to enhance growth due to high protein content.  Bacteria, main component biofloc, can produce polyhydroxybutyrate (PHB) as reserve of energy and growth accelerator for fish. The aim of the research were to study the effect of the different C:N and C:P ratio of media on the content of polyhydroxybutyrate in biofloc and to determine optimum media to produce high polyhydroxybutyrate content in biofloc. The experiment was arranged in factorial  with completely randomized design  in  three replications.  Treatments were C:N ratio of 15, 20, 25 and C:P ratio of 75, 100, and 125. The result showed that C:N ratio and C:P ratio of media and their interaction  affect the content of polyhydroxybutyrate in biofloc.  C:N ratio of 20 and C:P ratio of 125 resulted in most polyhydroxybutyrate (29.25±7.376 mg g-1 biofloc dry weight). Ratio of  C:N  of media gave linier and quadratic responses and C:P ratio of media gave linier one. Optimum polyhydroxybutyrate production was obtained at C:N ratio of 20.9 and C:P ratio of  125 resulting in 29.66 mg  g-1 biofloc dry weight (2,97%)